The Solar Attraction Effect on Orbital Elements of the Moon - H. Saleh, Abdulrahman; Damin, Taif A. (Iraqi Journal of Science, 2022)
In this paper, the solar attraction effect on the Moon orbital elements had been studied. The solar attraction considered a third body perturbation. The initial values of the Moon orbital elements at 2015-1-21.5 which are used (semi major axis=380963.78 km, eccentricity =0.056o, Eular angles (Ω=30°, ω=40°, , i=18.4°). The Moon in a perigee of its orbit at the initial time. A program which designed, was used to calculate the Moon position ,velocity and orbital elements through the years (2015-2035). The position and velocity components of the Moon were calculated by solving the equation of Kepler for elliptical orbit using Newton Raphson's method for (1000) periods and hundred steps of time for each period. The results show a secular changes for the Moon orbital elements with solar attraction, and they will deviate from the initial values with many years.